Primary students’ ability to convert verbal expressions into mathematical models in fraction materials - Shanti Nurhidayah; Salsabila Anindiyah; Yudistira Indra Prahasta Putra Elwanda; Setiyani; Khodari, Rahmad; Gunawan (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to describe the patterns of errors and the forms of scaffolding needed by students to convert verbal expressions into mathematical models in fraction material. This research used a descriptive qualitative method. The research involved 4th-grade students from a selected elementary school in Cirebon City. Data were collected through tests and interviews. The instruments used were a written mathematical representation ability test and an interview question guide. The data analysis techniques employed included data reduction, data presentation, and conclusion drawing. The results showed that high-ability students effectively recognize numerators, denominators, and problem contexts, enabling accurate translation of verbal expressions into a mathematical model. Medium-ability students were able to answer most questions but still struggled to distinguish between numerators and denominators. On the other hand, low-ability students often had difficulty understanding verbal questions, which led to errors in writing fractions.